2020
DOI: 10.1039/d0ra06250b
|View full text |Cite
|
Sign up to set email alerts
|

Controlled preparation of multiple mesoporous CoAl-LDHs nanosheets for the high performance of NOx detection at room temperature

Abstract: By fine tuning the metal mole ratio, CoAl-LDHs (CA) with a 2D nanosheet structure were successfully prepared via a one-step hydrothermal method using urea as both precipitator and pore-forming agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Whether Co5/Fe1 or Co-LDHs, the main peak of the O 1s moves in the direction of low binding energy as the current density increases, suggesting that water molecules react with the Co or Fe active sites. The peaks located at 531.4 (Co–OH, Co-LDHs) and 532.8 eV (Co–OH, Co5/Fe1) shifted to 530 (Co-LDHs) and 531.3 eV (Co5/Fe1) as the reaction proceeds, which may be due to the presence of the Co–O absorption peak, and the emergence of Co–O and Co–O–H implies the generation of Co–O–OH. ,, It is worth noting that Co5/Fe1 has a relatively rapid migration under the initial current density, indicating a stronger reaction response. To Co-LDHs, it is shown that the main peak of O 1s in XPS spectra first widens during the prior reaction because of the increased proportion of surface-adsorption-O (ads.…”
Section: Resultsmentioning
confidence: 99%
“…Whether Co5/Fe1 or Co-LDHs, the main peak of the O 1s moves in the direction of low binding energy as the current density increases, suggesting that water molecules react with the Co or Fe active sites. The peaks located at 531.4 (Co–OH, Co-LDHs) and 532.8 eV (Co–OH, Co5/Fe1) shifted to 530 (Co-LDHs) and 531.3 eV (Co5/Fe1) as the reaction proceeds, which may be due to the presence of the Co–O absorption peak, and the emergence of Co–O and Co–O–H implies the generation of Co–O–OH. ,, It is worth noting that Co5/Fe1 has a relatively rapid migration under the initial current density, indicating a stronger reaction response. To Co-LDHs, it is shown that the main peak of O 1s in XPS spectra first widens during the prior reaction because of the increased proportion of surface-adsorption-O (ads.…”
Section: Resultsmentioning
confidence: 99%
“…The metal ratios in the final LDHs heavily influence their morphology, and consequently, their performance as sensors. Wang et al controlled the Co-to-Al ratio in CoAl-LDHs synthesized via hydrolysis for optimal electrochemical NO x detection [84]. Aqueous solutions with varying ratios of Co(NO 3 ) 2 •6H 2 O and Al(NO 3 ) 3 •9H 2 O were treated with urea for hydrothermal treatment.…”
Section: Hydro(solvo)thermal Synthesismentioning
confidence: 99%
“…25 Wang et al prepared hexagonal nanosheets Co-Al LDHs with a complete structure and uniform distribution via a one-step hydrothermal method; these materials showed a high sensing performance for 100 ppm NO x (17.09) and a fast response time (4.27 seconds). 26 Gheibi et al reported that their fabricated Ni-Cr-Al LDHs sensor had a response/ recovery time to acetone gas at room temperature of approximately several minutes. 27 The Ni-Fe-Al LDHs were prepared by a one-step hydrothermal method, and showed an 82% response to 100 ppm NO x at room temperature.…”
Section: Introductionmentioning
confidence: 99%